2018
DOI: 10.7861/clinmedicine.18-1-75
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and management of cerebral venous thrombosis

Abstract: Cerebral venous thrombosis (CVT) is rare and accounts for 0.5% of all strokes. Its clinical presentation is variable and diagnosis requires a high index of clinical suspicion in conjunction with neuroradiological diagnostic support. Treatment options are limited and are mostly based on consensus. Therefore, familiarity with international guidelines is important. Outcome is often good and most patients make a full recovery, although a small proportion suffers death or disability. Here, we describe the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 34 publications
1
97
0
11
Order By: Relevance
“…Systemic administration of fibrinolytic agents such as urokinase to recanalize thrombosed pathways has been attempted but strong evidence regarding its safety and efficacy is lacking (9). Endovascular thrombolysis may also be considered in patients who are unresponsive and deteriorating, despite aggressive medical treatment (10). Siddiqui et al, in their systematic review assessing mechanical thrombectomy with or without intrasinus thrombolysis suggested that this approach is safe (46).…”
Section: Anticoagulation In Cvstmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic administration of fibrinolytic agents such as urokinase to recanalize thrombosed pathways has been attempted but strong evidence regarding its safety and efficacy is lacking (9). Endovascular thrombolysis may also be considered in patients who are unresponsive and deteriorating, despite aggressive medical treatment (10). Siddiqui et al, in their systematic review assessing mechanical thrombectomy with or without intrasinus thrombolysis suggested that this approach is safe (46).…”
Section: Anticoagulation In Cvstmentioning
confidence: 99%
“…However, this figure rises to 15% of all young strokes in the Asian population (8, 9). The commonest site of origin of thrombosis is believed to be the junction of cerebral veins and larger sinuses (10). Several disorders can cause or predispose patients to CVST such as genetic and acquired prothrombotic disorders, cancer, hematological diseases, vasculitis, systemic inflammatory disorders, pregnancy, puerperium, and infections.…”
Section: Introductionmentioning
confidence: 99%
“…Following the acute-phase treatment, long-term anticoagulants such as Vitamin K antagonist (warfarin) should be continued with a target to achieve an international normalized ratio of 2–3. [79] Currently, direct oral anticoagulants (DOACs) are gaining attention as potential therapy in CVST. In the acute-phase treatment, DOACs have been found to be comparable with warfarin in preventing the recurrence of venous thromboembolism.…”
Section: Management Of Cvstmentioning
confidence: 99%
“…The diagnosis is typically based on clinical suspicion and confirmatory neuroimaging. Formerly, the reports of thrombosis were made using angiography; however, today CTV and MRV can be used as reliable alternatives to confirm the diagnosis (11,35,37,38).…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis is typically based on clinical suspicion and confirmatory neuroimaging findings. Cerebral veins and sinuses can be examined using the following different methods (37).…”
Section: Diagnosismentioning
confidence: 99%